Student Management in Mulia Private School Rantang Village Hamparan Perak District - Aldi Nasution; Candra Wijaya (Universitas Muhammadiyah Enrekang, 2023)
This study aims to describe student management that takes place at Mulia Private School in Rantang City Village. This study used descriptive qualitative method. Data collected by interview, observation and documentation study. In this study, the subjects of the study were the principal, vice principal in student affairs and several students and teachers in the subject area of ​​this school. This study shows that the ongoing student management process is in accordance with the scope of student management, and was prepared by the school in accordance with technical instructions from the education office.